Free-riding or internalizing? An opportunistic view on decentralization versus centralization - Fabio Fiorillo; Agnese Sacchi (Center for Economic Studies and ifo Institute (CESifo), 2011)
The aim of the paper is to analyze a model of local public good provision with positive interjurisdictional spillovers comparing decentralized and centralized system. As in the recent Second Generation Theory (SGT) of fiscal federalism (Seabright 1996; Lockwood 2002, 2006; Besley and Coate 2003; Weingast 2009), we also adopt a political economy approach, assuming different behaviours of political leaders (Leviathan and non-Leviathan). The main contribution of the paper is to consider two relevant aspects neglected by the political economy models: the size of local jurisdictions and the explicit definition of the rent-seeking behaviour. Moreover, modelling interregional externalities as a mechanism contributing to lowering the production cost of the public good in each region, a different trade-off - from the traditional and new theory of fiscal federalism - is proposed in order to compare decentralized versus centralized solution: the gains from internalizing externalities and the losses of freeriding advantages, which may differ with regional size and preferences for the public good. Given this general framework, the convenience of decentralization versus centralization mainly depends on the interaction among these factors: i) the free-riding gains exploiting positive externalities; ii) the gains of internalizing externalities; iii) the degree of preferences heterogeneity; iv) the implicit transfers ('cross subsidization') across different regions. To summarize, from a positive viewpoint, decentralization should not be necessarily pursued only in the absence of externalities, but also with high spillovers. The key insight of this result is represented by different size of regions, which may determine an asymmetry among citizens' responses concerning the best institutional setting.
Keywords: H73; H77; H41; D72; 330; decentralization; spillovers; free-riding; rent-seeking behaviour; local public goods; Lokales öffentliches Gut; Spillover-Effekt; Internalisierung externer Effekte; Finanzföderalismus; Trittbrettfahrerverhalten; Rent Seeking; Theorie